Role of antigen specific antibodies in the immunopathogenesis of extrinsic allergic alveolitis induced by avian antigens - De Beer, P. M (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Med.Biochemistry)) -- University of Stellenbosch, 1991.